Effects of alongshore morphology on groundwater flow and solute transport in a nearshore aquifer. Issue 2 (14th February 2016) - Zhang, Ying; Li, Ling; Erler, Dirk V.; Santos, Isaac; Lockington, David
Abstract: Variations of beach morphology in both the cross‐shore and alongshore directions, associated with tidal creeks, are common at natural coasts, as observed at a field site on the east coast of Rarotonga, Cook Islands. Field investigations and three‐dimensional (3‐D) numerical simulations were conducted to study the nearshore groundwater flow and solute transport in such a system. The results show that the beach morphology, combined with tides, induced a significant alongshore flow and modified local pore water circulation and salt transport in the intertidal zone substantially. The bathymetry and hydraulic head of the creek enabled further and more rapid landward intrusion of seawater along the creek than in the aquifer, which created alongshore hydraulic gradient and solute concentration gradient to drive pore water flow and salt transport in the alongshore direction within the aquifer. The effects of the creek led to the formation of a saltwater plume in groundwater at an intermediate depth between fresher water zones on a cross‐shore transect. The 3‐D pore water flow in the nearshore zone was also complicated by the landward hydraulic head condition, resulting in freshwater drainage across the inland section of the creek while seawater infiltrating the seaward section. These results provided new insights into the complexity, intensity, and time scales of mixing among fresh groundwater, recirculating seawater and creek water in three dimensions. The 3‐D characteristics of nearshore pore water flow and solute transport have important implications for studies of submarine groundwater discharge and associated chemical input to the coastal sea, and for evaluation of the beach habitat conditions. Key Points: 3‐D nearshore groundwater flow and solute transport at a field site are examined Tidal creek causes complex morphological and hydraulic variations, inducing alongshore flow and solute transport Cross‐shore and alongshore flow and solute transport processes interact strongly in the near‐creek area